Evaluating the use of laparoscopic gastrostomy in children with congenital heart disease in Colombia: a retrospective analysis - Chaparro-Zaraza, Diego Fernando; Pinilla-Orejarena, Adriana Patricia; Otoya-Castrillón, Juan Pablo; Chacón-Valenzuela, Daniella; Quintero-Olarte, Juan Jose; Cifuentes-Rincón, Angélica Belen; Quesada-Uribe, Bryan Felipe; Durán-Hernandez, Alvaro; Bermon, Anderson; Manrique-Hernandez, Edgar Fabian (Frontiers in Pediatrics, 2024)
Introduction: Congenital Heart Disease (CHD) is the most common congenital disorder and a leading cause of infant mortality. Despite improved survival rates, patients with CHD often face malnutrition due to increased metabolic demands, feeding difficulties, and gastrointestinal dysfunction. Malnutrition in CHD is linked to poor short and long-term clinical outcomes. Gastrostomy (GT) is frequently used for long-term enteral support, and laparoscopic GT (LGT) has demonstrated advantages in children without CHD. This study evaluated a modified Georgeson’s percutaneous LGT technique and its perioperative complications in children with CHD. Methods: We performed an analytical retrospective cohort study from 2018 to 2022, including patients younger than 24 months with a diagnosis of CHD who underwent LGT. The primary outcome evaluated was the presence of complications during surgery and the first thirty postoperative days. Complications were graded using Clavien-Dindo´s (CD) classification. Sociodemographic, clinical, and procedure-related variables were collected. A bivariate analysis was performed using STATA 15, and a p<0.05 was considered statistically significant. Results: Seventy-eight patients were eligible (male 56.41%, Median age 129.5 days, weight: 4.83 kg). The median surgery time was 35 minutes. The complication rate was 24.36%. The most frequent complications were GT site infection (10.26%), followed by leakage (8.97%) and granuloma formation (6.41%). Conversion to open surgery was significantly associated with postoperative complications (p=0.002). Conclusion: This modified technique is well-tolerated in children with CHD, demonstrating a low rate of CD grade 3A/3B complications and no grade 4 or 5 complications.